Plasma heating and confinement in the GOL-3 multiple mirror trap - Burdakov, A.V.; Arzhannikov, A.V.; Astrelin, V.T.; Ivanov, I.A.; Ivantsivsky, M.V.; Koidan, V.S.; Mekler, K.I.; Polosatkin, S.V.; Postupaev, V.V.; Rovenskikh, A.F.; Sinitsky, S.L.; Sulyaev, Yu.S. (Вопросы атомной науки и техники, 2005)
Experiments on plasma confinement in a multiple mirror configuration are carried out at GOL-3 facility in Novosibirsk. Feature of experiments at this facility is high plasma density (up to 5⋅10²¹ m⁻³ ). High ion temperature (up to 2 keV) essentially differs the regime with multimirror configuration from previously studied plasma heating by the Ebeam in a uniform magnetic field. Physical mechanism of effective heating of plasma ions, substantially dependent on corrugation of the magnetic field is discussed. In this paper the new experimental data from the GOL-3 facility are presented and the main attention to a stage of ion heating is addressed. Експерименти по нагріванню й утриманню плазми в багатопробковій пастці проводяться на установці ГОЛ- 3 у Новосибірську. Особливістю плазми в цій пастці є її відносно висока (до 5⋅10²¹ м⁻³ ) густина. Нагрівання плазми релятивістським електронним пучком у багатопробковій пастці істотно відрізняється від нагрівання в простому соленоїді тим, що спостерігається збільшення іонної температури аж до 2 кэВ. У роботі обговорюється механізм швидкого нагрівання іонів і представляються нові експериментальні результати, отримані на установці ГОЛ-3. Эксперименты по нагреву и удержанию плазмы в многопробочной ловушке проводятся на установке ГОЛ-3 в Новосибирске. Особенностью плазмы в этой ловушке является ее относительно высокая (до 5⋅10²¹ м⁻³ ) плотность. Нагрев плазмы релятивистским электронным пучком в многопробочной ловушке существенно отличается от нагрева в простом соленоиде тем, что наблюдается увеличение ионной температуры вплоть до 2 кэВ. В работе обсуждается механизм быстрого нагрева ионов и представляются новые экспериментальные результаты, полученные на установке ГОЛ-3.